2013
DOI: 10.1111/dmcn.12140
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of tests to predict cerebral palsy in young children

Abstract: CUSCranial ultrasound GMA General movements assessment IVH Intraventricular haemorrhage STARD Standards for Reporting Diagnostic Accuracy AIM This systematic review evaluates the accuracy of predictive assessments and investigations used to assist in the diagnosis of cerebral palsy (CP) in preschool-age children (<5y).METHOD Six databases were searched for studies that included a diagnosis of CP validated after 2 years of age. The validity of the studies meeting the criteria was evaluated using the Standards f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
437
1
31

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(484 citation statements)
references
References 65 publications
(264 reference statements)
15
437
1
31
Order By: Relevance
“…41,42 A combination of TEA MR imaging findings and 3-month CA general movement assessment demonstrates improved predictive validity over TEA MR imaging alone, [43][44][45] so evaluation of the relationships between this early MR imaging scoring system and concurrent clinical measures and the combination of early MR imaging and clinical measures to predict later outcomes is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 A combination of TEA MR imaging findings and 3-month CA general movement assessment demonstrates improved predictive validity over TEA MR imaging alone, [43][44][45] so evaluation of the relationships between this early MR imaging scoring system and concurrent clinical measures and the combination of early MR imaging and clinical measures to predict later outcomes is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, absence of these FM at 10 -15 weeks' postterm accurately predicts the development of cerebral palsy. 3 Where in the brain FM arise and how they are generated remain unclear. However, the absence of FM in infants with periventricular lesions of the corona radiata or internal capsule 4 suggests that projections between the cortex and spinal cord may contribute to these movements.…”
mentioning
confidence: 99%
“…According to a review 23 there is good evidence that GMs assessment can accurately predict the development of CP. In our study, infants who had persistant abnormal GMs showed CP sypmtoms and those who had normal GMs demonstrated normal neurologic development at a corrected age of 12 months, which supports findings in the literature.…”
Section: Group Imentioning
confidence: 99%